Centre and periphery in king Agrippa´s speech: Josephus´ interpretation of roman hegemony in the Flavian Age (First Century C.E.): Centro e periferia no discurso do rei Agrippa II: uma interpretação Josefiana sobre a dominação Romana na Era Flaviana (Século I E.C.) (Revista de História da UEG (REVHIST), 2023)
In this article we will discuss how the Jewish historian Flavius Josephus interpreted the roman hegemony as it appears in king Agrippa II´s speech in the Jewish War. This speech was addressed to the Jews in Jerusalem in the eve of the first Jewish war against Rome. The roman hegemony will be studied through the imperial concept of centre/periphery relationship which is rooted in geography. We will argue that Josephus did not use a concept of centre/periphery relationship which was common in the Augustan Age. Instead, Josephus used a concept that was common during the Flavian Age. For Josephus the root of the roman power was the roman army which was always in the move. Therefore, we believed that his interpretation of the roman hegemony, in the speech of the king Agrippa II, was related politically and theologically to the Greek tradition of fortune as it appears in the Greek historian Polybius. But his interpretation of roman hegemony is also connected with his Jewish ancestral tradition that can be identified with the “quietist” movement.Keywords: Roman Empire. Agrippa II. Centre/Periphery. Quietism.